1993
DOI: 10.3346/jkms.1993.8.2.153
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of c-erbB-2 gene product increase in stomach cancer cell lines

Abstract: c-erbB-2 oncogene encodes a growth factor receptor whose amino acid sequence has extensive homology with human epidermal growth factor receptor. It is frequently overexpressed in human breast, ovary, lung, and stomach cancers, where its overexpression is related significantly to the prognosis. Tl investigate the possible role of c-erbB-2 oncogene in the oncogenesis of stomach cancer, we examined the genetic alterations of c-erbB-2 oncogene in 4 stomach cancer cell lines, SNU-1, SNU-5, SNU-16 and KATO III. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…As shown in Figure 2, synthesis rate of erb B-2 protein in SNU-1 cells was increased compared to SNU-16 cells while the half-life of erb B-2 protein was not significantly different ( Figure 1). This enhanced protein synthesis rate was also observed in SNU-5 cells, showing erb B-2 protein overexpression without mRNA increase (Bae et al, 1993;1996).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…As shown in Figure 2, synthesis rate of erb B-2 protein in SNU-1 cells was increased compared to SNU-16 cells while the half-life of erb B-2 protein was not significantly different ( Figure 1). This enhanced protein synthesis rate was also observed in SNU-5 cells, showing erb B-2 protein overexpression without mRNA increase (Bae et al, 1993;1996).…”
Section: Discussionmentioning
confidence: 62%
“…In addition to overexpression of erb B-2 at mRNA level, several reports suggested that post-transcriptional upregulation of c-erb B-2 might exist (Burhing et al, 1995;Oshima et al, 1995;Child et al, 1999). We earlier reported post-transcriptional overexpression of erb B-2 (Bae et al, 1993). In that study, erb B-2 protein level was upregulated without mRNA increase in SNU-1 and SNU-5 stomach cancer cells compared to SNU-16 or KATO III cells.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…4). The variant 4b was highly expressed in most of metastasis‐related gastric cancer cell lines, which include KATO III, MKN74, and Hs746T (derived from metastatic site), SNU1 and SNU16 (derived from poorly differentiated tumors 27 with overexpression of ERBB2/HER2/neu 28, 29), and the highly metastatic cell line MKN45P 45. Similar high expression of variant 4b was observed in stomach tumor tissue (derived from metastatic adenocarcinoma).…”
Section: Discussionmentioning
confidence: 66%
“…KATO III, MKN74, and Hs746T were derived from metastatic sites. SNU1 and SNU16 were established from poorly differentiated tumors 27 and shown overexpression of ERBB2 ( HER2/neu ) that have been related to metastatic ability 28, 29. Stomach tumor tissue was derived from adenocarcinoma isolated from 77‐year‐old female Caucasian, the metastases of which were seen in lymph nodes.…”
Section: Resultsmentioning
confidence: 99%